Incidence and prevalence trends of youth‐onset type 2 diabetes in a cohort of Canadian youth: 2002‐2013. Issue 4 (27th December 2017) - Amed, Shazhan; Islam, Nazrul; Sutherland, Jenny; Reimer, Kim
Abstract : Objective: Youth‐onset type 2 diabetes is an emerging disease. We estimated incidence and prevalence trends of youth‐onset type 2 diabetes between 2002 and 2013 in the Canadian province of British Columbia. Methods: This population‐based cohort study used a validated diabetes case‐finding definition and algorithm to differentiate type 2 from type 1 diabetes to identify youth <20 years with type 2 diabetes within linked population‐based administrative data. Age‐standardized incidence and prevalence were calculated. JoinPoint regression and double exponential smooth modeling were used. Results: From 2002/2003 to 2012/2013, the incidence of youth‐onset type 2 diabetes increased from 3.45 (95% confidence interval, CI: 2.43, 4.80) to 5.16 (95% CI: 3.86, 6.78)/100 000. The annual percent change (APC) in incidence was 3.74 (95% CI: 1.61, 5.92; P  = 0.003) overall, while it was 5.94 (95% CI: 1.84, 10.20; P  = 0.009) and 0.53 (95% CI: −5.04, 6.43; P  = 0.837) in females and males, respectively. The prevalence increased from 0.009% (95% CI: 0.007, 0.011) in 2002/2003 to 0.021% (95% CI: 0.018, 0.024) in 2012/2013 with an APC of 7.89 (95% CI: 6.41, 9.40; P  < 0.0001). In females, it increased from 0.012% (95% CI: 0.009, 0.015) to 0.027% (95% CI: 0.023, 0.032) and in males from 0.007% (95% CI: 0.005, 0.009) to 0.015% (95% CI: 0.012, 0.019). By 2030, we forecast a prevalence of 0.046% (95% CI: 0.043, 0.048). Conclusions: Youth‐onset type 2 diabetes is increasing with higher rates in females vs males. If these rates continue, in 2030, the number of cases will increase by 5‐fold. These data are needed to set priorities for diabetes prevention in youth.